Blistering Distal Dactylitis in an Adult. Issue 4 (July 2015) - Kollipara, Ramya; Downing, Christopher; Lee, Michael; Guidry, Jacqueline; Robare-Stout, Samantha; Tyring, Stephen
Background: Blistering distal dactylitis is a localised infection of the anterior pad of the distal phalanx of the digits. It most commonly affects children and uncommonly adults with a history of immunosuppression or trauma. Objective: A case of blistering distal dactylitis in a 32-year-old male is reported. The patient was not immunocompromised and did not report trauma. Conclusion: Blistering distal dactylitis may rarely present in adults (including those who are not immunocompromised or reporting trauma) and thus should be in the differential diagnosis for an adult presenting with bullae at the fingertips. The differential diagnosis for this presentation also includes herpetic whitlow, epidermolysis bullosa, bullous impetigo, and friction blisters.